Microbial production of medium-chain length polyhydroxyalkanoates. (March 2021) - Silva, Juliana B.; Pereira, João R.; Marreiros, Bruno C.; Reis, Maria A.M.; Freitas, Filomena
Highlights: Medium-chain length poly(hydroxyalkanoates), biopolymers with valuable properties. Defined and renewable substrates for sustainable mcl-PHA production. Engineering biosynthesis of mcl-PHA for diversity. Conventional and alternative downstream approaches for PHA recovery. Abstract: Medium-chain-length poly(hydroxyalkanoates), mcl-PHAs, are naturally produced polymers characterized by material properties that include low crystallinity and low melting and glass transition temperatures, which render them suitable for diverse applications. These biodegradable and biocompatible biopolymers are accumulated as intracellular energy and carbon reserves by a wide range of bacteria, mainly, of the genus Pseudomonas . Despite their valuable properties, mcl-PHAs commercial development is still limited, mostly due to the high costs associated with their production and extraction. To overcome such problems, several approaches are being pursued comprising: the search for higher yielding strains, both wild-type and engineered bacteria; the utilization of low-cost feedstocks, such as wastes; and the development of environmentally and economically sustainable downstream procedures for polymer recovery and purification. Intensive research is also being done for the development of mcl-PHA-based materials for use in different areas, especially in high-value applications, such as biomedicine and drug delivery, in which the product's performance may justify its higher cost.